Modeling a fluid power drive of the excavator equipment - Yaryzhko, Alexander; Ярижко, Олександр Володимирович (Харківський національний автомобільно-дорожній університет, 2021)
The article studies an example of simulation of complex technical systems that combine the dy-namics of the excavator equipment and the fluid power drive mechanical subsystem.
Моделювання об’ємного гідропривода екскаваторного обладнання
Keywords: simulation model; excavator working equipment; mechanical systems; SimScape; SimHydraulics; SimMechanics; імітаційна модель; робоче обладнання екскаватора; механічні системи; 621.879; 10.30977/BUL.2219-5548.2021.92.1.178